Dicer monitoring in a model filamentous fungus host, Cryphonectria parasitica - Aulia, Annisa; Tabara, Midori; Telengech, Paul; Fukuhara, Toshiyuki; Suzuki, Nobuhiro (Current Research in Virological Science, 2020)
The ascomycete Cryphonectria parasitica has served as a model filamentous fungus for studying virus host interactions because of its susceptibility to diverse viruses, its genetic manipulability and the availability of many biological and molecular tools. Cryphonectria prasitica is known to activate antiviral RNA silencing upon infection by some viruses via transcriptional up-regulation of key RNA silencing genes. Here, utilizing a newly developed GFP-based reporter system to monitor dicer-like 2 (dcl2) transcript levels, we show different levels of antiviral RNA silencing activation by different viruses. Some viruses such as mycoreovirus 1, a suppressor-lacking mutant of Cryphonectria hypovirus 1 (CHV1-Δp69) and Rosellinia necatrix partitivirus 11 (RnPV11) highly induced RNA silencing, while others such as CHV3, Rosellinia necatrix victorivirus 1 and RnPV19 did not. There was considerable variation in dcl2 induction by different members within the family Hypoviridae with positive-sense single-stranded RNA genomes or Partitiviridae with double-stranded RNA genomes. Northern blotting and an in vitro Dicer assay developed recently by us using mycelial homogenates validated the reporter assay results for several representative virus strains. Taken together, this study represents a development in the monitoring of Dicer activity in virus-infected C. parasitica. •A reporter system was developed to monitor transcriptional dicer induction in Cryphonectria parasitica.•GFP green fluorescence manifested dicer induction upon virus infection.•Green fluorescence intensity varied between different viruses.•A simple in vitro assay for dicer enzymatic activity was established.•Estimated enzymatic activity agreed with transcriptional induction level.